2019
DOI: 10.1097/qad.0000000000002070
|View full text |Cite
|
Sign up to set email alerts
|

Extremely low hepatitis C prevalence among HIV co-infected individuals in four countries in sub-Saharan Africa

Abstract: A multicentric, retrospective case-series analysis (facility-based) in five sites across Kenya, Malawi, Mozambique, and Uganda screened HIV-positive adults for hepatitis C virus (HCV) antibodies using Oraquick rapid testing and viral confirmation (in three sites). The results reveal a substantially lower prevalence than previously reported for these countries, suggesting that targeted integration of HCV screening in African HIV programs may be more impactful than routine screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 16 publications
(14 reference statements)
0
15
0
Order By: Relevance
“…Our findings are consistent with those reported in HIV-positive pregnant women from Cameroon (7.7%), 25 higher than to reported in Nigeria (0.5%), 26 Botswana (3.1%), 27 Rwanda (4.1%), 19 and Sudan (5.6%), 28 but is lower than that reported in Ethiopia (12.1%), 12 and Ghana (14.9%). 29 The proportion of HIV/HCV co-infection observed in our cohort was compared to reported in southern (3.3%) and north (42.3%) of sub-Saharan Africa, 30 and European countries (12.3%). 31 Most of the time, high HIV/HBV coinfection is attributed to the fact they share mutual routes of transmission.…”
Section: Discussionmentioning
confidence: 83%
“…Our findings are consistent with those reported in HIV-positive pregnant women from Cameroon (7.7%), 25 higher than to reported in Nigeria (0.5%), 26 Botswana (3.1%), 27 Rwanda (4.1%), 19 and Sudan (5.6%), 28 but is lower than that reported in Ethiopia (12.1%), 12 and Ghana (14.9%). 29 The proportion of HIV/HCV co-infection observed in our cohort was compared to reported in southern (3.3%) and north (42.3%) of sub-Saharan Africa, 30 and European countries (12.3%). 31 Most of the time, high HIV/HBV coinfection is attributed to the fact they share mutual routes of transmission.…”
Section: Discussionmentioning
confidence: 83%
“…The prevalence demonstrated in this review was higher in Mozambique (30/2600 [1.15%]) than in Malawi (2/385 [0.5%]), Uganda (18/7400 [0.24%]) or Kenya (10/4500 [0.22%]). 43 While an HBV–HIV prevalence of 32.0% (168/531) was demonstrated in Cameroon, 44 a systematic review reported that among 8162 participants in Ghana, there was a pooled prevalence of 13.6% for HBV–HIV co-infection. 45 …”
Section: Discussionmentioning
confidence: 99%
“…10 15 16 This is especially high when compared with the general population HCV prevalence in Kenya of <1%-4%. 17 18 However, multiple barriers exist at individual, provider and system levels resulting in low rates of testing, engagement in care and completion of treatment courses for PWID. [19][20][21] Although less than 20% of PWID with chronic HCV worldwide have undergone antibody screening, the number who have completed PCR confirmatory testing is even lower.…”
Section: Open Accessmentioning
confidence: 99%